An Aircraft Ranging Algorithm Based on Two Frames of Image in Monocular Image Sequence - Fu, Xiaoning; Wang, Lixia (Defence Science Journal, 2014)
We proposed a novel rotation-invariant feature based passive ranging algorithm to estimate the distance of an imaged non-cooperation target to camera. This improved algorithm avoids sometimes occurrence of physically unreasonable results in solving the existing quartic equation, such as the happening of complex or negative value. This method uses three matched points in two adjacent frames of an image sequence to extract depth-dependent line features of the target. With this line features combination of the observer’s displacement and imaging directions, a quadratic equation was build to estimate the distance. Analysis shows that the proposed new passive ranging equation would be solvable when the observer is with non-zero displacement in adjacent sampling instances. Our reduced-model experiment also demonstrates that the proposed algorithm is not only simple and feasible but also with a relative ranging error no more than 4 per cent in most cases. Defence Science Journal, Vol. 64, No. 1, January 2014, DOI:10.14429/dsj.64.2887